Effects Teacher Certification and Teacher Commitment on Teacher Performance (International Journal of Scientific Research and Management (IJSRM), 2017)
Purpose - The purpose of this study was to analyze the effect of teacher certification and teacher commitment to teacher performance.Design / Methodology / Approach - The analysis technique in this study is using Structural Equation Modeling (SEM) with AMOS 18 program. Sampling is using random sampling, to the e-commerce users. Some 450 respondents took part and the size of the sample that can be used is 180 after the selection process.Findings and implications - First: stated that the certification of teachers significantly influence the performance of teachers is received. Second: stated that the certification of teachers significantly influence the performance of Limitations - Although the justification for using sample based on ethnic and regional divisions in the country of Indonesia for research related to teacher certification is already exist in the literature, this sample may not reflect the actual total teacher population in the world